Demand for rainfall-index based insurance: a case study from Morocco - McCarthy, Nancy (International Food Policy Research Institute, 2003)
In this paper, we derive estimates for willingness to pay for rainfall-index based insurance contracts. Surveys were undertaken in four regions in Morocco, representing different mean and variability of rainfall conditions. Results indicate that respondents in the high variability regions preferred contracts that paid out more often (had higher rainfall trigger levels), and which were more costly. In fact, a strong majority of respondents indicated they would purchase these contracts at the fair-value price; the estimated median willingness to pay for such contracts was between 12-20 percent above the fair value contract. However, in the lower rainfall variability regions, the cheaper contracts with lower trigger values were the only contracts for which the estimated median willingness to pay was greater than the fair-value of the contract. Finally, estimated coefficients for explanatory variables such as human and physical assets, debt levels, etc. did not have consistent impacts, either across or within regions.